2023
DOI: 10.1002/ecy.4004
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology influences butterfly nectar foraging on non‐native plants in an oak savanna

Abstract: The negative impacts of non‐native species have been well documented, but some non‐natives can play a positive role in native ecosystems. One way that non‐native plants can positively interact with native butterflies is by provisioning nectar. Relatively little is known about the role of phenology in determining native butterfly visitation to non‐native plants for nectar, yet flowering time directly controls nectar availability. Here we investigate the phenological patterns of flowering by native and non‐nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Differences in phenology between native and introduced plants have also had implications for pollinators. A recent study found that introduced plants flowered later than natives in an endangered savanna ecosystem, likely because of the increased drought‐tolerance of the introduced relative to the natives (Rivest et al., 2023). As a result, the native butterflies were entirely dependent on the nectar provided by introduced plants at the end of the season (Rivest et al., 2023).…”
Section: General Thesis: Maintaining Stability In Ecosystem Function ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Differences in phenology between native and introduced plants have also had implications for pollinators. A recent study found that introduced plants flowered later than natives in an endangered savanna ecosystem, likely because of the increased drought‐tolerance of the introduced relative to the natives (Rivest et al., 2023). As a result, the native butterflies were entirely dependent on the nectar provided by introduced plants at the end of the season (Rivest et al., 2023).…”
Section: General Thesis: Maintaining Stability In Ecosystem Function ...mentioning
confidence: 99%
“…A recent study found that introduced plants flowered later than natives in an endangered savanna ecosystem, likely because of the increased drought‐tolerance of the introduced relative to the natives (Rivest et al., 2023). As a result, the native butterflies were entirely dependent on the nectar provided by introduced plants at the end of the season (Rivest et al., 2023). Given a lack of historical data, it is unclear whether the introduced plants have extended (i.e., provided new resources) or maintained the length of the season (i.e., replacing native resources) in this ecosystem (Rivest et al., 2023).…”
Section: General Thesis: Maintaining Stability In Ecosystem Function ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main limitations of this study are as follows: (1) Data were collected solely from urban waterfront green spaces, and the limited types of urbanization studied may only represent part of the urban butterfly community; (2) This study focused only on the overall impact of urbanization on butterfly diversity, without fully considering factors such as climate change, land cover type [58], ecological corridor connectivity [59], nectar plants [60], host plants [61,62], predators, and competitors [63]. (3) This study primarily concentrated on the summer season, potentially missing out on capturing seasonal and annual changes in butterfly populations.…”
Section: Limitations and Perspectivesmentioning
confidence: 99%